(untitled) (Global Journal of Human-Social Science, 2023)
In this article delivered originally as an address to the Australian Academy of Forensic Sciences on its fiftieth anniversary the author a past President reflects on the past present and future of the Academy In the review of the past he recalls the personality of Dr O R Schmalzbach who founded the Academy and initiated the successful mix of topics and members in the first 25 years He then reviews the changes that came about producing the present Academy with more women members scientists and less ceremony Looking to the future he concludes that there will be no going back to the old ways However he suggests initiatives to broaden the definition of forensic sciences beyond primary attention to bench science He also encourages the revival to some degree of the participation of the leaders of the medical and legal professions and their engagement with the issues of science and society or forensic sciences broadly envisaged